Steel Production Process in CV. XYZ: Proses Produksi Baja di CV. XYZ - Setyawan, Agus Setyawan; Wulandari, Indah Apriliana Sari (Universitas Muhammadiyah Sidoarjo, 2024)
The construction services sector plays a vital role in national development, encompassing economic, social, and cultural dimensions. This study focuses on CV. XYZ, a company specializing in steel construction, specifically examining the production process of hollow fences. The research aims to ascertain the time and costs required for hollow fence fabrication and to develop a Bill of Materials (BOM) for hollow fences. The methodology involves observing the production process and conducting cost analysis. Results reveal insights into production efficiency, cost implications, and material requirements for hollow fence manufacturing. This study contributes to optimizing production processes and cost-effective resource utilization in the steel construction industry, facilitating informed decision-making for stakeholders. Highlights : Steel construction company examines hollow fence production process. Research aims to determine time, costs, and develop BOM for hollow fences. Study contributes to optimizing production and cost-effective resource utilization. Keywords : Construction services, steel construction, hollow fences, production efficiency, cost analysis.